Preliminary study of offshore wind turbine foundation in Malaysia - Muhammad Ammar, Nik Mu’tasim; Muhammad Hatifi, Mansor; Hadi, Abdul Salaam (Springer, 2023)
One of the most promising prospects being actively researched and implemented is the offshore wind turbine. The offshore wind turbine has proven to have great potential when looking to supply high amounts of clean and renewable energy. However, here in Malaysia, wind turbines productions are limited. In this study, the aim is to determine a potential installation of wind turbine. Wind data are determined, and a model of wind turbine are then subjected to the loading to analyze its movement and foundation in these different conditions. In this paper, a design study is presented which aims to encounter the problem involving the offshore wind turbine structure and analyze the structures load transferred to the surrounding soil. This paper also reviews previous research work and then presents a simple dynamic system of calculations along with free body diagrams to help define this problem. The model is developed and simulated with SIMULINK to obtain time domain force distribution. The results are then applied into the equations of motion to analyse the relationship between the turbine and soil foundation dynamics. The conclusion of this design analysis will help designers determine the best design for offshore wind turbine foundations and allow offshore wind turbines to be implemented in Malaysian region.